Efficiency Gains from Trade Reform : Foreign Input Technology or Import Competition? Evidence from South Africa - Shendy, Riham (Taylor and Francis, 2013)
The empirical trade literature examining the effect of tariff reductions on productivity commonly proxies the former with Nominal Tariff Rates (NTR) and estimates the latter as the production function residual. In the context of the South African trade reform experience, we examine the different channels by which tariff cuts affect productivity growth. Using industry-level data for the manufacturing sector and covering the reform period from 1994 to 2004, we disentangle the differential effect of increased foreign competition, proxied by reductions in NTR, and that of the imported technology, proxied by the reductions in Input Tariff Rates (ITR), on productivity growth. Our measure of efficiency growth controls for the effect of tariff reductions on markups. The results suggest that the efficiency difference between foreign and domestic inputs has a major effect on productivity gains. Declines in ITR significantly raise productivity growth compared to an insignificant effect for NTR. Additionally, we find that higher protection rates are associated with higher markups, albeit this finding is not robust across all specifications.